Impersonation dan Dark Jokes sebagai Tindakan Cyberbullying dalam Fenomena Bahasa “Anak Jaksel” di Media Sosial Twitter - Nadya Poernamasari (Journal of Social, Culture, and Language, 2023)
Language is a variety of spoken and non-spoken which becomes verbal and non-verbal language in the communication science. The presence of the “Anak Jaksel" language as a popular culture in Indonesia is present through diction or special word equivalents such as (literally, which is, prefer). The main objective of this study is to find cyberbullying in texts on social media, Twitter. In social media, issues and phenomena are experienced as part of social construction. This research is a qualitative research using a descriptive analysis method. The researcher uses the observation method on social media with texts that are entered in searches through the hashtag #AnakJaksel, as well as literature studies. The dominant pattern of cyberbullying in this study is impersonation and dark jokes. The existence of "Anak Jaksel" is marked by the diction that is repeatedly expressed. This reinforcement then appears with the identity that is formed afterwards, namely by making the process of imitating and joking in dark jokes an act of cyberbullying that is formed. Cyberbullying is a form of social construction with the role of “Selebtwit” as social actors. Keywords: Cyberbullying, Social Media, Bahasa Anak Jaksel